PENGGUNAAN MEDIA VISUAL BERBENTUK “ULAR TANGGA NUMERASI” UNTUK MENINGKATKAN PEMAHAMAN PERKALIAN PADA ANAK BERKEBUTUHAN KHUSUS - Nugraha, Adi (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
This research aims to investigate the impact of using visual media in the form of numeration snakes and ladders to improve understanding of multiplication in children with special needs at SD Negeri 1 Dodogan with the implementation time when the campus is assigned to teach class 7. The research method involves pre-test and post-test with the subject of 5 children special needs slow learner. The results of data analysis showed that there was quite a significant improvement after using the numeracy snakes and ladders learning media for 10 meetings. The pre-test and post-test results showed an increase from 46% to 77% in students’ multiplication operation abilities after treatment. Learning through the snakes and ladders game increases students’ active participation and social skills, while making the learning process fun. The implications of this research include the need for a gradual approach and delivery of the use of visual media, so that students who want to use it do not experience difficulties.